1995
DOI: 10.1103/physreve.51.3729
|View full text |Cite
|
Sign up to set email alerts
|

Boson-fermion transmutation and the statistics of anyons

Abstract: It is shown that, by allowing a transmutation between a boson and a fermion, the system with both bosons and fermions will have the statistical distribution function of an anyon. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Therefore, such particles and their thermodynamic properties have been the subject of research by a number of authors [21,22,23,24,25]. The statistical weight of N identical particles occupying a group of G states for bosons or fermions is, respectively, given by…”
Section: Thermodynamic Properties Of Ideal Gas Of Fractional Statistimentioning
confidence: 99%
“…Therefore, such particles and their thermodynamic properties have been the subject of research by a number of authors [21,22,23,24,25]. The statistical weight of N identical particles occupying a group of G states for bosons or fermions is, respectively, given by…”
Section: Thermodynamic Properties Of Ideal Gas Of Fractional Statistimentioning
confidence: 99%
“…Particles with the new statistics were named "anyons" by Wilczek [15]. The thermodynamic properties of systems with fractional statistical particles or anyons have been considered and some factorizable properties of these systems were introduced by Huang [16]. It has been shown that the thermodynamic quantities of a free anyon gas may be factorized to ideal Bose and Fermi gases [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that this procedure does not yield a nonperturbative information. We will review a nonperturbative approach based on the factorizable properties of thermodynamic quantities of the anyon gas in the next section [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have been done in the context of many-body quantum mechanics. In recent papers [13,14], Wu and others had derived the occupation-number distribution function of the anyon gas to formulate the theory of quantum statistical mechanics, with the help of the idea of fractional exclusion statistics [15]. In that paper [13], Wu also obtained the second viral coefficient and found that the "statistical interaction" may be attractive or repulsive, depending on the statistical parameter.…”
Section: Introductionmentioning
confidence: 99%